Genetic Characterization of the Soybean Nested Association Mapping Population. Issue 2 (1st July 2017) - Song, Qijian; Yan, Long; Quigley, Charles; Jordan, Brandon D.; Fickus, Edward; Schroeder, Steve; Song, Bao‐Hua; Charles An, Yong‐Qiang; Hyten, David; Nelson, Randall; Rainey, Katy; Beavis, William D; et al.
Abstract : A set of nested association mapping (NAM) families was developed by crossing 40 diverse soybean [ Glycine max (L.) Merr.] genotypes to the common cultivar. The 41 parents were deeply sequenced for SNP discovery. Based on the polymorphism of the single‐nucleotide polymorphisms (SNPs) and other selection criteria, a set of SNPs was selected to be included in the SoyNAM6K BeadChip for genotyping the parents and 5600 RILs from the 40 families. Analysis of the SNP profiles of the RILs showed a low average recombination rate. We constructed genetic linkage maps for each family and a composite linkage map based on recombinant inbred lines (RILs) across the families and identified and annotated 525, 772 high confidence SNPs that were used to impute the SNP alleles in the RILs. The segregation distortion in most families significantly favored the alleles from the female parent, and there was no significant difference of residual heterozygosity in the euchromatic vs. heterochromatic regions. The genotypic datasets for the RILs and parents are publicly available and are anticipated to be useful to map quantitative trait loci (QTL) controlling important traits in soybean.